Articles and Structures Using Colorable Electrostatic Dissipative (ESD) Polycarbonate Blends
A polycarbonate and crystalline polyester blend with an inherently dissipative polymer and transesterification inhibitor addresses the limitations of traditional ESD materials by achieving sub-ohmic surface resistivity and colorability, enhancing electrostatic dissipation and processing efficiency.
Patent Information
- Application Number
- JP2023572720
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-05-28
- Filing Date
- 2022-05-27
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2042-05-27
AI Technical Summary
Conventional electrostatic dissipative (ESD) materials used in polymers are limited by their natural darkness, making them difficult to color and often require high processing temperatures that can damage antistatic agents, while intrinsically dissipative polymers (IDPs) struggle to achieve low enough surface resistivity without darkening the material.
A composition comprising polycarbonate copolymer, crystalline polyester, and an inherently dissipative polymer, along with a transesterification inhibitor, achieves sub-ohmic surface resistivity and allows for colorability by using a blend that includes polycarbonate copolymers like ITR-BPAPC and PBT, ensuring low processing temperatures to maintain ESD properties.
The composition provides a wide color space for pigmentation while maintaining effective electrostatic dissipation, impact resistance, and processing performance, overcoming the limitations of traditional ESD materials by achieving surface resistivities as low as 1×10^9 ohms and allowing for easy coloration.
Smart Images

Figure 0007607802000012 
Figure 0007607802000013 
Figure 0007607802000014
Abstract
Description
[Technical field]
[0001] FIELD OF THE DISCLOSURE The present disclosure relates to static dissipative polycarbonate blends, and in particular to colorable static dissipative polycarbonate blends. [Background technology]
[0002] Electrostatic discharge can be detrimental to electronic components, resulting in breakdowns, reduced reliability, and increased costs, as well as potential component failures in deployed equipment. Polymeric materials are generally good insulators, but can be made conductive or electrostatic dissipative by the addition of conductive fillers, such as metal fillers, nonconductive fillers coated with a metal coating, or conductive nonmetallic fillers, as well as carbon-based fillers such as carbon nanotubes, carbon fibers, and carbon black. The addition of such materials creates a network of interconnected particles within the polymer matrix, allowing charge to be conducted through the insulating polymer. Electrostatic dissipative (ESD) and antistatic materials are widely used in various fields such as semiconductors, consumer electronics, and industrial construction to prevent the accumulation of static electricity. These two types are defined by their surface resistivity (SR), in which the former is 1×10 6 Ohms to 1×10 9 between ohms, and the latter 1×10 10 Ohms to 1×10 12 ohms. Classical ESD materials are generally not colorable, since they are limited by the natural blackness or darkness of the conductive carbon fillers. Conversely, those compounds doped with conventional inherently dissipative polymers (IDPs) (to achieve electrostatic behavior) have a colorless appearance, yet can be colored at a density of 1×10 9 It is not possible to achieve a surface resistivity as low as 1×10 ohms. 9 There remains a need in the art for materials that have a surface resistivity (low to low ohms) while also maintaining a colorable appearance. Summary of the Invention [Means for solving the problem]
[0003] An embodiment of the present disclosure comprises from about 1 wt.% to about 99 wt.% polycarbonate copolymer resin; from about 1 wt.% to about 70 wt.% crystalline polyester resin; from about 0.1 wt.% to about 50 wt.% essentially dissipative polymer; and from about 0.001 wt.% to about 10 wt.% transesterification inhibitor, with a molecular weight of 1×10 or more as measured according to ASTM D257. 9 A polymeric composition exhibiting a surface resistivity of less than ohms, wherein the combined weight percentage of all components does not exceed about 100 wt.%, all weight percentages being based on the total weight of the polymeric composition.
[0004] In yet another aspect, the present disclosure relates to a method of forming a composition including a polycarbonate copolymer, a crystalline polyester, an inherently dissipative polymeric additive, and a transesterification inhibitor.
[0005] In certain aspects, the present disclosure relates to a method of forming an article comprising molding an article from the polymeric compositions described herein.
[0006] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate several aspects and, together with the description, serve to explain the principles of the disclosure. [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 depicts Table 5 showing the formulations and properties of C-1, C-2, and EX-2. [Diagram 2] FIG. 2 depicts Table 6 showing the formulations and properties of C-3, EX-2, EX-3, EX-4, EX-5, EX-6, and EX-7. [Diagram 3] FIG. 3 depicts Table 7 showing the formulations and properties of EX-8, EX-9, and EX-10. [Figure 4]Figure 4A shows an image of a molded plate comprising sample EX-2, and Figure 4B shows an image of a molded plate comprising conventional conductive carbon black-filled polycarbonate, sample C-3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Given the complexity and sensitivity of microelectronic devices, controlling electrostatic discharge is becoming increasingly difficult. Even at low voltages, such electrostatic discharges can cause severe damage to sensitive devices. Electrostatic dissipative (ESD) and antistatic materials are widely used in various fields such as semiconductors, consumer electronics, and industrial construction to prevent the accumulation of static electricity. These two types are defined by their surface resistivity (SR), in terms of which the former is 1×10 6 Ohms to 1×10 9 between ohms, and the latter 1×10 10 From 1×10 12 Thus, a variety of different electrostatic dissipative (ESD) materials can be used to avoid the build-up of static electricity on plastics during manufacture or use.
[0009] However, the incorporation of electrostatic dissipative materials (antistatic agents) into a variety of different substrates or polymer resin matrices has its own limitations. Polymers generally require high temperature processing, which can damage or destroy the antistatic agent, thus negating the ESD properties. Furthermore, many higher molecular weight ESD agents are incompatible with the particular substrate or matrix polymer used. The use of antistatic agents may also provide only temporary ESD properties to the compositions in which they are used. Performance and effectiveness are also limited by environmental conditions such as humidity. Conventional ESD materials also contain conductive fillers such as carbon fibers, conductive carbon black, graphite, graphene, and carbon nanotubes, which generally also impart a dark color to the composition. Thus, conventional ESD materials cannot be easily colored, as the color space may be limited by the natural blackness of the conductive carbon fillers. Furthermore, conventional inherently dissipative polymer (IDP) doped compounds, while not darkened by additives, typically have a color of less than 1×10 9 Although surface resistivity values as low as ohms may not be attainable, the formulations of the present disclosure achieve both ESD and broad colorability while maintaining desirable electrical, impact, and processing performance.
[0010] The present disclosure provides compositions of colorable electrostatic dissipative (ESD) compounds comprising polycarbonate (PEI) doped with an inherently dissipative polymer (IDP) and a crystalline polymer such as polybutylene terephthalate (PBT) or poly(1,4-cyclohexylene dimethylene 1,4-cyclohexylene dicarboxylate) (PCCD). These compositions have a colorability of at least 1×10 9 The ability to provide a low surface resistivity (SR) of up to ohms makes these compositions fully pigmentable and suitable for ESD applications. The impact, thermal, and flow properties are also desirable for manufacturing.
[0011] In one embodiment, the disclosed composition comprises about 1 wt.% to about 99 wt.% of a polycarbonate copolymer resin; about 1 wt.% to about 70 wt.% of a crystalline polyester resin; about 0.1 wt.% to about 50 wt.% of an essentially dissipative polymer; and about 0.001 wt.% to about 10 wt.% of a transesterification inhibitor. The polymer composition has a molecular weight of 1×10 as measured according to ASTM D257. 9 It may exhibit a surface resistivity of less than ohms.Furthermore, the combined weight percentage of all components does not exceed about 100 wt.%, with all weight percentages being based on the total weight of the polymer composition.
[0012] Before the present compounds, compositions, articles, systems, devices, and / or methods are disclosed and described, it is to be understood that they are not limited to particular synthetic methods, unless otherwise specified, or to detailed reagents, unless otherwise specified, and as such may, of course, vary. It is also to be understood that the terminology used herein is for the purpose of describing detailed embodiments only, and is not intended to be limiting.
[0013] Various combinations of elements of the present disclosure are encompassed by the present disclosure, for example combinations of elements from dependent claims that are dependent on the same independent claim.
[0014] Further, it will be understood that unless expressly stated otherwise, it is in no way intended that any method described herein be construed as requiring that its steps be performed in a specific order. Thus, where a method claim does not actually recite the order in which its steps are to be followed, or where the steps are not otherwise specifically indicated in the claim or specification to be limited to a specific order, no order is intended to be inferred in any respect. This applies to any possible non-express basis for interpretation, including logical considerations regarding the sequence of steps or the flow of operations; the plain meaning derived from grammatical constructions and punctuation; and the number or type of embodiments described herein.
[0015] All publications mentioned herein are incorporated by reference to disclose and describe the methodologies and / or materials in connection with which the publications are cited. definition
[0016] It is also understood that the terms used herein are for the purpose of describing detailed aspects only and are not intended to be limiting. As used herein and in the claims, the term "comprising" can include "consisting of" and "consisting essentially of" embodiments. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this disclosure belongs. In this specification and in the claims that follow, reference will be made to several terms that are intended to be defined herein.
[0017] As used in this specification and the appended claims, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. Thus, for example, reference to a "polycarbonate" includes a mixture of two or more polycarbonate polymers.
[0018] As used herein, the term "combination" is inclusive of blends, mixtures, alloys, reaction products, and the like.
[0019] Ranges can be expressed herein as from one value (a first value) to another value (a second value). When such a range is expressed, the range, in some embodiments, includes one or both of the first and second values. Similarly, when values are expressed as approximations, it will be understood that the particular value is another embodiment of the use of the antecedent "about." It will further be understood that the endpoints of each range are valid both in relation to the other endpoint, and independent of the other endpoint. It will also be understood that there are multiple values disclosed herein, and that each value is also herein disclosed as "about" that value, in addition to the particular value itself. For example, if the value "10" is disclosed, then "about 10" is also disclosed. It will also be understood that each unit between two particular units is also disclosed. For example, if 10 and 15 are disclosed, then 11, 12, 13, and 14 are also disclosed.
[0020] As used herein, the terms "about" and "at or near" mean that the quantity or value in question can be the specified value, approximately the specified value, or about the specified value. As used herein, unless otherwise indicated or inferred, the value is generally understood to be a variation of ±10% of the nominal value indicated. The term is intended to convey that the equivalent result or effect described in the claims is promoted by such similar values. That is, it is understood that the amounts, sizes, formulations, parameters, and other quantities and characteristics are not and do not have to be exact, but can be approximate and / or larger or smaller as desired, reflecting tolerances, conversion factors, rounding, measurement errors, and the like, and other factors known to those skilled in the art. In general, the amounts, sizes, formulations, parameters, or other quantities or characteristics are "about" or "approximate", whether or not they are expressly defined as such. When "about" is used before a quantitative value, the parameter is also understood to include the specific quantitative value itself, unless otherwise specifically defined.
[0021] As used herein, the term "optional" or "optionally" means that the subsequently described event or circumstance may or may not occur, and that the description includes instances in which the event or circumstance occurs and instances in which the event or circumstance does not occur. For example, the phrase "optional additive" means that the additive may or may not be included, and that the description includes both polymer compositions with and without additional additives.
[0022] In one aspect, "substantially free" may refer to less than 0.5 wt.%, or less than about 0.5 wt.%, being present in a given composition or component. In another aspect, substantially free may be less than 0.1 wt.%, or less than about 0.1 wt.%. In another aspect, substantially free may be less than 0.01 wt.%, or less than about 0.01 wt.%. In yet another aspect, substantially free may be less than 100 parts per million (ppm), or less than about 100 ppm. In yet another aspect, substantially free may refer to an amount that is below detectable levels, if present at all. Substantially free or free may further refer to a component that was not added or incorporated into the composition.
[0023] Disclosed are not only the components used to prepare the compositions of the present disclosure, but also the compositions themselves used within the methods disclosed herein. These and other materials are disclosed herein, and it is understood that when disclosing combinations, subsets, interactions, groups, etc. of these materials, each of the various individual and collective combinations and permutations of these compounds are not expressly disclosed as specifically mentioned, but each is specifically contemplated and described herein. For example, when a particular compound is disclosed and discussed, and multiple modifications that can be made to multiple molecules that include the compound are discussed, what is specifically contemplated is each and every combination and permutation of the compound and modifications that are possible, unless otherwise specifically indicated to the contrary. Thus, when a class of molecules A, B, and C is disclosed, as well as a class of molecules D, E, and F, and an example of a combination molecule AD is disclosed, this means that each is individually and collectively contemplated, even if each is not individually mentioned, and the combinations AE, AF, BD, BE, BF, CD, CE, and CF are considered to be disclosed. Similarly, any subsets or combinations of these are disclosed. Thus, for example, the subgroups AE, BF, and CE may be considered as disclosed. This concept applies to all aspects of this application, including but not limited to steps in the methods of making and using the disclosed compositions. Thus, where there are various additional steps that can be performed, it is understood that each of these additional steps can be performed with any specific aspect or combination of aspects of the disclosed method.
[0024] In this specification and the appended claims, reference to parts by weight of a particular component or ingredient in a composition or article indicates the weight relationship, expressed in parts by weight, between that component or ingredient and the other components or ingredients in the composition or article. Thus, in a compound containing 2 parts by weight of component X and 5 parts by weight of component Y, X and Y are present in a weight ratio of 2:5, and are present in such ratio regardless of whether additional components are included in the compound.
[0025] Weight percentages of components are based on the total weight of the formulation or composition in which the component is included, unless specifically stated to the contrary.
[0026] As used herein, the terms "weight percent," "wt%," and "wt.%" may be used interchangeably and refer to the weight percent of a given component based on the total weight of the composition, unless otherwise specified. That is, all wt% values are based on the total weight of the composition, unless otherwise specified. It is to be understood that the sum of the wt% values of all components in a disclosed composition or formulation equals 100.
[0027] Unless otherwise stated herein to the contrary, all testing standards are the latest standards in effect at the time of filing this application.
[0028] Each of the materials disclosed herein is commercially available and / or methods for its preparation are known to those of skill in the art.
[0029] It is understood that the compositions disclosed herein have specific functions. Disclosed herein are specific structural requirements that perform the disclosed functions, and it is understood that there are various structures that can perform the same functions associated with the disclosed structures, and that these structures typically achieve the same results. Polymer Resin
[0030] In an embodiment, the polymer composition may comprise a polymer resin. In various embodiments, the polymer resin may comprise a thermoplastic resin or a thermosetting resin. The thermoplastic resin may comprise polypropylene, polyethylene, ethylene-based copolymers, polyamide, polycarbonate, polyester, polyoxymethylene (POM), polybutylene terephthalate (PBT), polyethylene terephthalate (PET), polycyclohexylene dimethylene terephthalate (PCT), liquid crystal polymer (LPC), polyphenylene sulfide (PPS), polyphenylene ether (PPE), polyphenylene oxide-polystyrene blend, polystyrene, high impact modified polystyrene, acrylonitrile-butadiene-styrene (ABS) terpolymer, acrylic polymer, polyetherimide (PEI), polyurethane, polyetheretherketone (PEEK), polylactic acid (PLA)-based polymer, polyethersulfone (PES), and combinations thereof. The thermoplastic resin may also comprise a thermoplastic elastomer, such as polyamide and polyester-based elastomers. The base substrate may also include blends of the above resins and / or other types of combinations. In various embodiments, the polymeric resin may include a thermosetting polymer. Suitable thermosetting resins may include phenolic resins, urea resins, melamine-formaldehyde resins, urea-formaldehyde latex, xylene resins, diaryl phthalate resins, epoxy resins, aniline resins, furan resins, polyurethanes, or combinations thereof.
[0031] In a specific embodiment, the polymer composition comprises a polycarbonate, specifically a polycarbonate copolymer, a polycarbonate homopolymer, or a combination thereof. As used herein, "polycarbonate" refers to an oligomer or polymer containing one or more residues of dihydroxy compounds, such as dihydroxy aromatic compounds, linked by carbonate bonds, and includes homopolycarbonates, copolycarbonates, and (co)polyestercarbonates. The terms "residue" and "structural unit" used with respect to components of a polymer are synonymous throughout this specification. The terms "BisA", "BPA", or "bisphenol A" can be used interchangeably and, as used herein, refer to the formula (1): [ka] BisA refers to a compound having the structure represented by the formula: BisA can also be called 4,4'-(propane-2,2-diyl)diphenol; p,p'-isopropylidenebisphenol; or 2,2-bis(4-hydroxyphenyl)propane. BisA has the CAS Registry Number 80-05-7.
[0032] Combinations of polycarbonate with other thermoplastic polymers can be used, such as homopolycarbonates, copolycarbonates, and combinations of polycarbonate copolymers with polyesters. Useful polyesters include, for example, poly(alkylene dicarboxylates), liquid crystal polyesters, and polyester copolymers. The polyesters described herein are generally completely miscible with polycarbonates when blended.
[0033] In a further example, the polycarbonate of the polymeric resin can include a branched polycarbonate. An exemplary branching agent can include, but is not limited to, 1,1,1-tris(4-hydroxyphenyl)ethane (THPE). As a further example, the branched polycarbonate resin can be end-capped with a suitable end-capping agent, such as p-cyanolphenol (known as HBN).
[0034] The polymeric resin may include a polycarbonate copolymer including units derived from BPA, or a mixture of one or more polycarbonate copolymers including units derived from BPA. In a specific example, the polymeric resin may include a polycarbonate copolymer having units derived from BPA and a poly(aliphatic ester)-polycarbonate copolymer derived from sebacic acid.
[0035] According to various embodiments, the polycarbonate may comprise high flow PC or low flow PC, or a combination thereof. High flow PC may be defined as a polycarbonate having a melt flow index (MFI) of greater than 10g / 10min at 300°C / 1.2kg. Low flow PC may be defined as a PC having an MFI of less than 10g / 10min at 300°C / 1.2kg when tested according to ASTM D1238.
[0036] In some embodiments, the polycarbonate copolymer component comprises a polyester-polycarbonate copolymer. As further described herein, the polyesters have the following formula (A): [ka] where T is the residue derived from terephthalic acid or its chemical equivalents, and D is the residue derived from the polymerization of ethylene glycol, butylene diol, specifically 1,4-butane diol, or its chemical equivalents.
[0037] In a specific embodiment, the polyester unit is derived from the reaction of isophthalic acid, terephthalic acid, and resorcinol (also known as ITR resins). The polyester unit has the following structure (B): [ka] where x corresponds to the molar ratio of isophthalate, y corresponds to the molar ratio of resorcinol, and z corresponds to the molar ratio of terephthalate, and x, y, and z add up to 100 percent of the polyester units. The concentration of polyester (ITR) resin can be at least 5%, based on the number of moles in the polymer. In a further embodiment, the polyester and polycarbonate are used in a molar ratio of about 5:95 to about 40:60, more specifically about 5:95 to about 35:65, depending on the desired properties. The polyester-polycarbonates can have a weight average molecular weight of about 1,500 to about 100,000, more specifically about 2,000 to about 40,000. The polyester-polycarbonate polymer can be a copolymer, particularly a block copolymer.
[0038] Specifically, the polyester units of the polyester-polycarbonate may be derived from the reaction of isophthalic diacid and terephthalic diacid (or derivatives thereof) with resorcinol, bisphenol A, or a combination comprising one or more of these, where the molar ratio of isophthalic acid units to terephthalic acid units is from 91:9 to 2:98, specifically from 85:15 to 3:97, more specifically from 80:20 to 5:95, and even more specifically from 70:30 to 10:90. When the polycarbonate comprises units derived from resorcinol and / or bisphenol A, the resorcinol carbonate may be used. The molar ratio of mixed isophthalate-terephthalate polyester units to bisphenol A carbonate units can be from 0:100 to 99:1, and the molar ratio of mixed isophthalate-terephthalate polyester units to polycarbonate units in the polyester-polycarbonate can be from 1:99 to 99:1, specifically from 5:95 to 90:10, more specifically from 10:90 to 80:20. When blends of polyester-polycarbonate and polycarbonate are used, the ratio of polycarbonate to polyester-polycarbonate in the blend can be from 1:99 to 99:1, specifically from 10:90 to 90:10, respectively.
[0039] In a specific embodiment, the polycarbonate copolymer may comprise a resorcinol-based aryl polyester or a resorcinol-based polyester carbonate polymer. ITR (isophthalate terephthalate resorcinol) resorcinol-based aryl polyesters, and "resorcinol-based polyarylesters," and "resorcinol-based polyarylates" are all intended to mean copolymers comprising resorcinol moieties and resorcinol-based ester linkages, and possibly other linkages such as resorcinol-based polycarbonate linkages. These terms are intended to include both polyesters containing only ester linkages, and polyester carbonates when resorcinol-based polycarbonate linkages are present. Thus, the polyester-polycarbonate copolymer may comprise repeating carbonate units of bisphenol A and repeating ester units, which may be any copolymer (C) of BPA polycarbonate and resorcinol phthalate (ITR), and for example (D). [ka]
[0040] These copolycarbonates can be synthesized by one skilled in the art or are commercially available, such as LEXAN™ SLX resins from SABIC, which are ITR-polycarbonate copolymers with molecular weights of 20,000-30,000 and refractive indices of about 1.59-1.603.
[0041] As an example, a resorcinol-based polyarylester may comprise both carbonate linkages (e.g., between resorcinol and bisphenol A moieties) and ester linkages (e.g., between resorcinol and isophthalic acid moieties). In an embodiment of the present disclosure, the composition comprises ITR-BPAPC.
[0042] In some instances, the resorcinol-based polyarylate resin may contain at least about 40 mole percent moieties derived from resorcinol. The resorcinol moieties may be introduced as the reaction product of reacting resorcinol or functionalized resorcinol with an aryl dicarboxylic acid or aryl dicarboxylic acid derivative suitable for forming an aryl ester bond with the resorcinol. Suitable dicarboxylic acid derivatives include, for example, carboxylic acid halides, carboxylic acid esters, and carboxylate salts.
[0043] The resorcinol-based polyarylates may further contain carbonate linkages derived from the reaction of a bisphenol with a carbonate-forming species, such as phosgene, making the resorcinol-based polyarylates polyestercarbonate copolymers. In another embodiment of the invention, the resorcinol polyarylate carbonate copolymers will comprise the reaction products of isophthalic and terephthalic acids, resorcinol, and optionally bisphenol A and phosgene. In one aspect, the resorcinol polyestercarbonate copolymers will be made to minimize the number of bisphenol dicarboxylic acid ester linkages, for example, by pre-reacting resorcinol with a dicarboxylic acid to form an aryl polyester block, and then reacting the aryl polyester block with a bisphenol and a carbonate portion to form the polycarbonate portion of the copolymer. Examples of resorcinol ester containing polymers can be found in U.S. Patent Nos. 6,861,482, 6,559,270, 6,265,522, 6,294,647, 6,291,589, and 5,916,997.
[0044] In another example, the polycarbonate copolymer may include polycarbonate dimethylbisphenol cyclohexane copolymer (DMBPC) that includes at least 50 mol% dimethylbisphenol cyclohexane monomer. DMBPC has the formula (E): [ka] where x and y represent the molar ratios of dimethylbisphenolcyclohexane and polycarbonate monomers, respectively. Thus, if x is 50, then y is 50, and the copolymer contains 50 mol % dimethylbisphenolcyclohexane and 50 mol % polycarbonate monomers. In some embodiments, x is 20 to 100.
[0045] In yet a further embodiment, the polyester-polycarbonate copolymer contains repeat units of formula (A) above, where D is a divalent radical derived from a dihydroxy compound, such as, for example, C 2-10 Alkylene radical, C 6-20 Alicyclic radical, C 6-20 T may be an aromatic radical or a polyoxyalkylene radical in which the alkylene group contains from 2 to 6 carbon atoms, in particular 2, 3, or 4 carbon atoms; T is a divalent radical derived from a dicarboxylic acid, for example C 2-10 Alkylene radical, C 6-20 Alicyclic radical, C 6-20 Alkyl aromatic radical, or C 6-20 It may be an aromatic radical.
[0046] In one embodiment, D is C 2-6 In another embodiment, D is an alkylene radical. [ka] wherein each R f are independently a halogen atom, C 1-10 Hydrocarbon group, or C 1-10is a halogen-substituted hydrocarbon group, n being 0 to 4. The halogen is typically bromine. Examples of compounds which may be represented by formula (7) include resorcinol, substituted resorcinol compounds such as 5-methylresorcinol, 5-ethylresorcinol, 5-propylresorcinol, 5-butylresorcinol, 5-t-butylresorcinol, 5-phenylresorcinol, 5-cumylresorcinol, 2,4,5,6-tetrafluororesorcinol, 2,4,5,6-tetrabromoresorcinol, or the like; catechol; hydroquinone; substituted hydroquinones such as For example, 2-methylhydroquinone, 2-ethylhydroquinone, 2-propylhydroquinone, 2-butylhydroquinone, 2-t-butylhydroquinone, 2-phenylhydroquinone, 2-cumylhydroquinone, 2,3,5,6-tetramethylhydroquinone, 2,3,5,6-tetra-t-butylhydroquinone, 2,3,5,6-tetrafluorohydroquinone, 2,3,5,6-tetrabromohydroquinone, or the like; or a combination comprising at least one of the foregoing compounds.
[0047] Examples of aromatic dicarboxylic acids that may be used to prepare the polyesters may include isophthalic or terephthalic acid, 1,2-di(p-carboxyphenyl)ethane, 4,4'-dicarboxydiphenyl ether, 4,4'-bisbenzoic acid, and mixtures comprising at least one of the foregoing acids. Acid-containing fused rings may also be present, for example in 1,4-, 1,5-, or 2,6-naphthalenedicarboxylic acid. Specific dicarboxylic acids are terephthalic acid, isophthalic acid, naphthalenedicarboxylic acid, cyclohexanedicarboxylic acid, or mixtures thereof. Specific dicarboxylic acids comprise mixtures of isophthalic acid and terephthalic acid, with the weight ratio of terephthalic acid to isophthalic acid being from 91:1 to 2:98. In another specific embodiment, D is C 2-6 is an alkylene radical and T is p-phenylene, m-phenylene, naphthalene, a divalent cycloaliphatic radical, or a mixture thereof. This class of polyesters includes the poly(alkylene terephthalates).
[0048] The polysiloxane-polycarbonate copolymer may be a useful polycarbonate copolymer and may contain 50 wt.% to 99 wt.% carbonate units and 1 wt.% to 50 wt.% siloxane units. Within this range, the polyorganosiloxane-polycarbonate copolymer may contain 70 wt.%, to 98 wt.%, more specifically 75 wt.% to 97 wt.% carbonate units and 2 wt.% to 30 wt.%, more specifically 3 wt.% to 25 wt.% siloxane units.
[0049] In one embodiment, the polysiloxane-polycarbonate copolymer can include 10 wt% or less, specifically 6 wt% or less, more specifically 4 wt% or less of polysiloxane based on the total weight of the polysiloxane-polycarbonate copolymer, can be generally optically clear, and is commercially available from Sabic under the designation EXL-T. In another embodiment, the polysiloxane-polycarbonate copolymer can include 10 wt% or more, specifically 12 wt% or more, more specifically 14 wt% or more of polysiloxane copolymer based on the total weight of the polysiloxane-polycarbonate copolymer, can be generally optically opaque, and is commercially available from Sabic under the designation EXL-P.
[0050] The polyorganosiloxane-polycarbonates can have a weight average molecular weight of 2,000 to 100,000 daltons, specifically 5,000 to 50,000 daltons, as determined by gel permeation chromatography using a crosslinked styrene-divinylbenzene column at a sample concentration of 1 milligram per milliliter and calibrated with polycarbonate standards.
[0051] Polyorganosiloxane-polycarbonates have a viscosity of 1 to 50 cubic centimeters per 10 minutes (cm), measured at 1.2 kilograms (kg) per 300 degrees Celsius (°C). 3 / 10 minutes), specifically 2 to 30 cm 3A mixture of polyorganosiloxane-polycarbonates of different flow properties can be used to achieve the overall desired flow properties.
[0052] Non-limiting examples of polysiloxane-polycarbonate copolymers include various copolymers available from Savic Corporation. In one embodiment, the polysiloxane-polycarbonate copolymer can have a polysiloxane content of 6% by weight based on the total weight of the polysiloxane-polycarbonate copolymer. In various embodiments, the 6% by weight polysiloxane block copolymer can have a weight average molecular weight (Mw) of about 23,000 to 24,000 Daltons using gel permeation chromatography with bisphenol A polycarbonate absolute molecular weight standards. In a particular embodiment, the 6% by weight siloxane polysiloxane-polycarbonate copolymer has a viscosity of about 10 cm at 300° C. / 1.2 kg. 310 minutes (see C9030T, a 6 wt% polysiloxane content copolymer available from Sabic as "transparent" EXL C9030T resin polymer). In another example, the polysiloxane-polycarbonate block may contain 20 wt% polysiloxane based on the total weight of the polysiloxane block copolymer. For example, a suitable polysiloxane-polycarbonate copolymer may be a bisphenol A polysiloxane-polycarbonate copolymer endcapped with para-cumylphenol (PCP) and having a polysiloxane content of 20% (see C9030P, available from Sabic as "opaque" EXL C9030P). In various embodiments, the weight average molecular weight of the 20% polysiloxane block copolymer can be from about 29,900 Daltons to about 31,000 Daltons when tested against polycarbonate standards using gel permeation chromatography (GPC) on a crosslinked styrene-divinylbenzene column and calibrated against a polycarbonate reference using a UV-VIS detector set at 264 nanometers (nm) on a 1 milligram per milliliter (mg / ml) sample eluted at a flow rate of about 1.0 ml / min. Further, the 20% polysiloxane block copolymer can be eluted at a flow rate of about 1.0 ml / min. 3 / 10 minutes and can exhibit siloxane domains ranging in size from about 5 microns to about 20 micrometers (microns, μm).
[0053] The composition may comprise from about 0.1 wt.% to about 99 wt.% of the polycarbonate copolymer. The PC copolymer component may be present in the polymer composition in a range of at least about 45 wt.% to about 85 wt.%. In further examples, the composition may comprise about 10 wt.% to about 90 wt.% polycarbonate copolymer, or about 10 wt.% to about 80 wt.% polycarbonate copolymer, or about 20 wt.% to about 80 wt.% polycarbonate copolymer, or about 25 wt.% to about 80 wt.% polycarbonate copolymer, or about 30 wt.% to about 80 wt.% polycarbonate copolymer, or about 40 wt.% to about 80 wt.% polycarbonate copolymer, or about 40 wt.% to about 75 wt.% polycarbonate copolymer, or about 45 wt.% to about 80 wt.% polycarbonate copolymer. In certain embodiments, at least 45 wt.% may enable the composition to reach a heat distortion temperature of at least, or at least about, 150° C., which may be beneficial for optimal application performance of the thermoplastic composition. For optimal performance within the range of the thermoplastic composition, 50-55 wt.%, or about 50-55 wt.%, is preferred.
[0054] In various embodiments, the disclosed compositions may comprise at least one crystalline polyester. The crystalline or semi-crystalline nature of a polymer may describe a polymer with organized or more tightly packed molecular chains. As a result, this highly organized molecular structure may provide a more defined melting point. These polymers have anisotropic flow, which may result in some dimensional instability as a result of greater shrinkage transverse to the flow than along the flow. Not only may the degree of crystallinity vary between different materials, but it may also vary within the same material. The degree of crystallinity may affect many properties of a polymer. Molecular weight and branching may affect crystallinity.
[0055] The at least one crystalline polyester can include polybutylene terephthalate (PBT), polycyclohexylene dimethylene terephthalate (PCT), polyethylene terephthalate (PET), polyethylene terephthalate glycol (PETG), polycyclohexylene dimethylene terephthalate glycol (PCTG), polycyclohexylene dimethylene terephthalate acid (PCTA), copolymers thereof, or combinations thereof, etc. In a detailed embodiment, the at least one crystalline polyester includes polybutylene terephthalate (PBT).
[0056] Particular embodiments of the composition include from about 1 wt.% to about 99 wt.% of at least one crystalline polyester, from 50 wt.% to about 97 wt.% of a thermoplastic resin, or from about 40 wt.% to about 97 wt.% of a polymeric resin, or from about 55 wt.% to about 97 wt.% of a polymeric resin, or from about 60 wt.% to about 97 wt.% of a polymeric resin, or from about 70 wt.% to about 97 wt.% of a polymeric resin, or from about 40 wt.% to about 95 wt.% of a polymeric resin, or from about 55 wt.% to about 95 wt.% of a polymeric resin, or from about 60 wt.% to about 95 wt.% of a polymeric resin, or from about 75 wt.% to about 97 wt.% of a polymeric resin.
[0057] In various aspects of the present disclosure, the thermoplastic resin can comprise a crystalline polyester. For example, the thermoplastic resin can comprise a polyalkylene ester (polyester), such as a polyalkylene terephthalate polymer.
[0058] As provided herein, polyesters have repeating units of the following formula (A) above. Chemical equivalents of diacids include dialkyl esters, such as dimethyl esters, diaryl esters, anhydrides, salts, acid chlorides, acid bromides, and the like. Chemical equivalents of ethylene diol and butylene diol include esters, such as dialkyl esters, diaryl esters, and the like. In addition to units derived from terephthalic acid or its chemical equivalent, and ethylene glycol or butylene diol, specifically 1,4-butane diol, or its chemical equivalent, other T and / or D units can be present in the polyester, provided that the type or amount of such units does not significantly adversely affect the desired properties of the thermoplastic composition. Poly(alkylene arylates) can have a polyester structure according to formula (A), where T comprises a group derived from aromatic dicarboxylates, alicyclic dicarboxylic acids, or derivatives thereof.
[0059] Examples of specifically useful T groups include, but are not limited to, 1,2-, 1,3-, and 1,4-phenylene; 1,4- and 1,5-naphthylenes; cis- or trans-1,4-cyclohexylene; and the like. Specifically, when T is 1,4-phenylene, the poly(alkylene arylate) is a poly(alkylene terephthalate). In addition, for poly(alkylene arylate), specifically useful alkylene groups D include, for example, ethylene, 1,4-butylene, and bis-(alkylene disubstituted cyclohexane), including cis- and / or trans-1,4-(cyclohexylene)dimethylene.
[0060] Examples of polyalkylene terephthalates include polyethylene terephthalate (PET), poly(1,4-butylene terephthalate) (PBT), and poly(propylene terephthalate) (PPT). Also useful are poly(alkylene naphthoates), such as poly(ethylene naphthanoate) (PEN), and poly(butylene naphthanoate) (PBN). A useful poly(cycloalkylene diester) is poly(cyclohexanedimethylene terephthalate) (PCT). Combinations comprising at least one of the foregoing polyesters may also be used.
[0061] Copolymers containing repeating ester units of alkylene terephthalate with other ester groups may also be useful. Useful ester units may include different alkylene terephthalate units, which may be present in the polymer chain as individual units or as blocks of poly(alkylene terephthalates). Specific examples of such copolymers include poly(cyclohexanedimethylene terephthalate)-co-poly(ethylene terephthalate), abbreviated as PETG when the polymer contains 50 mol% or more of poly(ethylene terephthalate), and PCTG when the polymer contains more than 50 mol% of poly(1,4-cyclohexanedimethylene terephthalate). Poly(cycloalkylene diesters) may also include poly(alkylene cyclohexane dicarboxylates). Of these, specific examples are of the formula (G): [ka] where R 2is a 1,4-cyclohexanedimethylene group derived from 1,4-cyclohexanedimethanol, and T is a cyclohexane ring derived from cyclohexanedicarboxylate or its chemical equivalent, and may comprise the cis-isomer, trans-isomer, or a combination comprising at least one of the foregoing isomers.
[0062] In another embodiment, the composition may further comprise a poly(1,4-butylene terephthalate) or "PBT" resin. PBT may be obtained by polymerizing a glycol component consisting of at least 70 mol%, preferably at least 80 mol%, tetramethylene glycol, and an acid or ester component consisting of at least 70 mol%, preferably at least 80 mol%, terephthalic acid and / or its polyester-forming derivatives. Commercially available examples of PBT include those available from SABIC™ under the trade names VALOX™ 315, VALOX™ 195, and VALOX™ 176, and have an intrinsic viscosity of 0.1 deciliters per gram (dl / g) to about 2.0 dl / g (or 0.1 dl / g to 2 dl / g) measured in a 60:40 phenol / tetrachloroethane mixture or similar solvent at 23 degrees Celsius (°C) to 30°C. In one embodiment, the PBT resin has an intrinsic viscosity of 0.1 dl / g to 1.4 dl / g (or about 0.1 dl / g to about 1.4 dl / g), specifically 0.4 dl / g to 1.4 dl / g (or about 0.4 dl / g to about 1.4 dl / g).
[0063] As described herein, the composition may comprise about 0.1 wt.% to about 99 wt.% crystalline polyester. In further examples, the composition may comprise about 0.1 wt.% to about 50 wt.% crystalline polyester, or about 0.1 wt.% to about 30 wt.% crystalline polyester, or about 0.1 wt.% to about 40 wt.% crystalline polyester, or about 0.1 wt.% to about 25 wt.% crystalline polyester, or about 0.1 wt.% to about 15 wt.% crystalline polyester, or about 1 wt.% to about 15 wt.% crystalline polyester, or about 1 wt.% to about 20 wt.% crystalline polyester, or about 0.5 wt.% to about 12 wt.% crystalline polyester. The polymer composition may comprise about 0.1 wt.% to about 70 wt.% crystalline polyester. Inherently dissipative polymers
[0064] In various embodiments, the disclosed polymer compositions can comprise an inherently dissipative polymer (IDP). An inherently dissipative polymer can refer to a polymer resin that has electrostatic dissipative (ESD) properties.
[0065] IDPs generally comprise modified polymers. In certain embodiments, IDPs may comprise thermoplastic elastomers, or modified thermoplastic elastomers. Such materials are generally described as polymers that have both hard and / or crystalline segments and / or blocks, and soft and / or rubbery segments and / or blocks in their backbone structure. These may be referred to as multi-block copolymers.
[0066] The IDPs disclosed herein may be ion doped. Conventionally, the IDPs may be doped with sodium ions. The IDPs of the present disclosure may be doped with phosphonium ions.
[0067] In some embodiments, the inherently dissipative polymer comprises a thermoplastic polyurethane (TPU), a polyolefin polyether copolymer, a thermoplastic polyester elastomer (COPE), a polyether block amide elastomer (COPA or PEBA), or a combination thereof. Examples of suitable copolymers include polyolefin-polyether copolymers, and the like.
[0068] As an example, the polymer composition may include an IDP comprising an ion-doped nylon (or polyamide) based multiblock copolymer, such as the commercially available Pelectron™ AS. Typical nylon based IDPs are by their nature detrimental to PC and cause degradation. However, the specific combination of components of the present disclosure may overcome this potential degradation. Processing temperatures are desirably kept as low as possible to prevent reaction of the IDP with PC and subsequent loss of surface conductivity. Its unique composition allows low temperature processing. Thus, processing temperatures may be kept below 240° C. for extrusion, compounding, and injection molding, especially extrusion and injection molding.
[0069] As a further example, the polymer composition may include a polymer masterbatch of a polymer resin system, such as an IDP comprising commercially available avanDISS™ 378.
[0070] In certain embodiments, the type of IDP selected may depend on the type of polycarbonate: for blends with polycarbonate copolymers, Pelectron™ AS was the preferred IDP, while AvanDISS™ was suitable for polycarbonate copolymer or polycarbonate homopolymer compositions.
[0071] The IDP should be approximately E+6 to E+8 ohms (e.g., 1×10 6 Ohms to 9×10 8 The IDP may have a surface resistivity in the order of ohms. The IDP may have a surface resistivity in the order of about E+4 to E+7 ohm-cm (e.g., 1×10 4 Ohms to 9×107 As an example, the IDP may have a volume resistivity of about 1×10 when tested in accordance with ASTM D257 on a 68 mm×68 mm×3 mm plaque specimen. 7 It may have a surface resistivity in ohms.
[0072] In some embodiments, the polymer composition may comprise about 0.1 wt.% to about 50 wt.% of the IDP. In further embodiments, the composition may comprise about 10 wt.% to about 50 wt.% of the IDP, or about 15 wt.% to about 50 wt.% of the IDP, or about 50 wt.% to about 70 wt.% of the IDP, or about 18 wt.% to about 40 wt.% of the IDP, or about 15 wt.% to about 45 wt.% of the IDP, or about 12 wt.% to about 35 wt.% of the IDP, or about 12 wt.% to about 40 wt.% of the IDP, or about 12 wt.% to about 50 wt.% of the IDP, or about 12 wt.% to about 50 wt.% of the IDP. Transesterification Inhibitors
[0073] The polymer composition may comprise one or more transesterification inhibitors. Transesterification inhibitors can inhibit the transesterification reaction of the polymer, thereby suppressing the polymerization reaction. Also, as is well known, the presence of transesterification inhibitors can inhibit the polymerization reaction. U.S. Pat. No. 4,069,278 teaches that no phosphorus-containing stabilizer (catalyst inhibitor) was added in the polycondensation of ethylene glycol and dimethyl terephthalate catalyzed by calcium acetate and antimony oxide.
[0074] Suitable transesterification inhibitors are well known in the art and can be selected from the group consisting of inhibitors of phosphorus-containing stabilizers such as pentaerythritol diphosphite (GE Specialty Chemicals, Parkersburg, WV, Ultranox™ 626), phosphoric acid, and polyphosphoric acid. Other examples are zinc diisopropyl dithiophosphate, tris(2,4-di-t-butylphenyl)phosphite, tris(mononylphenyl)phosphite, and mixtures thereof. Additional transesterification inhibitors include sodium dihydrogen phosphate, potassium acetate, trimethyl phosphate, and phenylphosphoric acid. Also included are orthophosphoric acid, represented by the formula xH2O·yP2O5, where x / y is 3, and polyphosphoric acid, which is called diphosphoric acid, triphosphoric acid, tetraphosphoric acid, and pentaphosphoric acid depending on the degree of condensation, and where 2DX / y>1, and mixtures thereof. Further examples include metaphosphoric acids represented by the formula xH2O·yP2O5, satisfying x / y=1, particularly trimetaphosphoric acid and tetrametaphosphoric acid, and ultraphosphoric acids having a network structure with a phosphorus pentoxide structure portion and satisfying 1>x / y>0 (these may be collectively referred to as "metaphosphate compounds"). Further examples include acid salts and esters of these phosphoric acids. Of these, cyclic sodium metaphosphate, ultra-region sodium metaphosphate, and diheptyl phosphate DHPA are advantageously used. As a specific example, the transesterification inhibitor may comprise a mixture of mono- and di-stearyl acid phosphate commercially available as AX71.
[0075] The transesterification inhibitor may be present in an amount of about 0.001 wt.% to about 10 wt.%, based on the total weight of the polymer composition. White pigment
[0076] In addition to the polycarbonate copolymer, the crystalline polyester, the IDP, and the transesterification inhibitor, the polymer composition of the present disclosure may further include a white pigment. The white pigment can impart opacity or a light opaque appearance to the polymer resin composition. In a further aspect, the white pigment can impart a white or off-white color to the polymer resin composition. Furthermore, these pigments tend to have high reflectance for both near infrared (NIR) and visible light. As used herein, reflectance can refer to the ability of a material to scatter light from its surface without absorbing light at a given wavelength.
[0077] Suitable white pigments may include titanium dioxide, zinc sulfide (ZnS), tin oxide, aluminum oxide (AlO3), zinc oxide (ZnO), calcium sulfate, barium sulfate (BaSO4), calcium carbonate (e.g., chalk), magnesium carbonate, antimony oxide (Sb2O3), white lead (basic lead carbonate, 2PbCO3·Pb(OH)2), lithopone (a combination of barium sulfate and zinc sulfide), sodium silicate, aluminum silicate, silicon dioxide (SiO2, i.e., silica), umo, clay, talc, metal-doped versions of the above materials, and combinations comprising at least one of the above materials. More specifically, the inorganic white pigment is selected from rutile or anatase titanium dioxide, zinc sulfide, and coated versions thereof, such as silanized titanium dioxide. A combination of different types of white pigments may be used. In a detailed embodiment, the white pigment may include titanium dioxide, antimony oxide, zinc oxide, white lead, or lithopone. In some embodiments of the present disclosure, talc may be used as a white pigment. Talc may be a suitable white pigment if the material has a color coordinate value high enough to give the material a white color. In one example, the color coordinate value is greater than 80. * Talc having a value of L (corresponding to the whiteness of a given material) can be a suitable white pigment as described herein.
[0078] The white pigment may have an average particle size of 0.01 to 10 micrometers (μm), specifically 0.05 μm to 1 μm, and more specifically 0.1 μm to 0.6 μm. The white pigment may be present in an amount of about 0.1 wt.% to about 50 wt.%. As an example, the composition may include titanium dioxide in an amount of 0.1 wt.% to 50 wt.%. In a further example, the composition may include titanium dioxide in an amount between 0.1 wt.% and 20 wt.%. Optical Agent
[0079] In a further aspect of the present disclosure, the polymer composition may include an optical agent. The optical agent may include an optical brightener. Examples of optical brighteners include optical brighteners (OBAs), fluorescent brighteners (FBAs), fluorescent whitening agents (FWAs), and the like, or a combination including at least one of the above optical brighteners. As used herein, an optical brightener refers to a dye that absorbs light in the ultraviolet and violet regions of the electromagnetic spectrum (usually about 340 to about 370 nm) and re-emits light in the blue region (usually about 420 to about 470 nm). These additives are often used to improve the color appearance of the polymer composition, causing a perceived "whitening" effect. The perceived whitening effect can make a given material appear less yellow by increasing the overall amount of blue light reflected. Exemplary optical brighteners are triazine-stilbenes (di-, tetra-, or hexa-sulfonated), coumarins, imidazolines, diazoles, triazoles, benzoxazolines, biphenyl-stilbenes, or the like, or a combination comprising at least one of the foregoing optical brighteners. In a detailed embodiment of the present disclosure, the optical agent may include, but is not limited to, 4,4'-bis(2-benzoxazolyl)stilbene, commercially available as Eastobrite™ OB-1 from Eastman, or 2,5-bis(5-tert-butyl-2-benzoxazolyl)thiophene, commercially available as Tinopal™ OB, or a combination thereof.
[0080] In certain embodiments, the composition comprises from about 0.001 wt.% to about 10 wt.% of an optical brightener. In further embodiments, the composition comprises from about 0.01 wt.% to about 5 wt.% of an optical brightener, or from about 0.01 wt.% to about 1 wt.% of an optical brightener. Additives
[0081] The disclosed thermoplastic composition may include one or more additives conventionally used in the manufacture of molded thermoplastic parts, provided that the optional additives do not adversely affect the desired properties of the resulting composition. Mixtures of optional additives may also be used. Such additives may be mixed at a suitable time during the mixing of the components to form the composite mixture. Exemplary additives may include UV agents, UV stabilizers, heat stabilizers, antistatic agents, antimicrobial agents, anti-drip agents, radiation stabilizers, pigments, dyes, fibers, fillers, plasticizers, fibers, flame retardants, antioxidants, lubricants, wood, glass, and metals, and combinations thereof.
[0082] The thermoplastic compositions disclosed herein can include one or more additional fillers. The fillers can be selected to provide additional impact strength and / or additional properties that can be based on the final selected properties of the polymer composition. In some embodiments, the fillers can include inorganic materials that can include clays, titanium oxide, asbestos fibers, silicate and silica powders, boron powders, calcium carbonates, talc, kaolin, sulfides, barium compounds, metals and metal oxides, wollastonite, glass spheres, glass fibers, flaky fillers, fibrous fillers, natural fillers and reinforcing agents, and reinforcing organic fibrous fillers.
[0083] Suitable fillers or reinforcing agents include, for example, granite, clay, feldspar, quartz, quartzite, perlite, tripoly, diatomaceous earth, aluminum silicate (mullite), synthetic calcium silicate, fused silica, fumed silica, sand, boron nitride powder, borosilicate powder, calcium sulfate, calcium carbonates (such as chalk, limestone, marble, and synthetic precipitated calcium carbonates), talc (including fibrous, modular, acicular, and lamellar talc), wollastonite, hollow or solid glass spheres, silicate spheres, cenospheres, aluminosilicates or (almospheres), kaolin, whiskers of silicon carbide, alumina, boron carbide, iron, nickel, copper, continuous and chopped carbon or glass fibers, molybdenum sulfide, zinc sulfide, barium titanate, barium ferrite, barium sulfate, barite, TiO2, acid Examples of suitable fillers include aluminum oxide, magnesium oxide, particulate or fibrous aluminum, bronze, zinc, copper, or nickel, glass flakes, flaked silicon carbide, flaked aluminum diboride, flaked aluminum, steel flakes, natural fillers such as wood flour, fibrous cellulose, cotton, sisal, jute, starch, lignin, ground nut shells, or rice hulls, reinforcing organic fibrous fillers such as poly(ether ketone), polyimide, polybenzoxazole, poly(phenylene sulfide), polyesters, polyethylene, aromatic polyamides, aromatic polyimides, polyetherimides, polytetrafluoroethylene, and poly(vinyl alcohol), as well as combinations comprising at least one of the foregoing fillers or reinforcing agents. The fillers and reinforcing agents can be coated with a layer of metallic material to promote electrical conductivity or can be surface treated, for example with silanes, to improve adhesion and dispersibility in the polymer matrix. Fillers may generally be used in amounts of 1 to 200 parts by weight, based on 100 parts by weight of the total composition.
[0084] In some embodiments, the thermoplastic composition may include a synergist. In various examples, the filler may function as a flame retardant synergist. The synergist, when added to a flame retardant composition, promotes improved flame retardancy over a comparable composition containing the same amounts of all the same components except for the synergist. Examples of mineral fillers that may function as synergists are granite, talc, calcium carbonate, dolomite, wollastonite, barium sulfate, silica, kaolin, feldspar, barite, or the like, or a combination that includes at least one of the preceding mineral fillers. Metallic synergists, such as antimony oxide, may also be used with the flame retardant. In one example, the synergist may include magnesium hydroxide and phosphoric acid. The mineral filler may have an average particle size of about 0.1 to about 20 μm, specifically about 0.5 to about 10 μm, and more specifically about 1 to about 3 μm.
[0085] The thermoplastic composition may include an antioxidant. The antioxidant may include either a primary or secondary antioxidant. For example, antioxidants include organic phosphites such as tris(nonylphenyl)phosphite, tris(2,4-di-t-butylphenyl)phosphite, bis(2,4-di-t-butylphenyl)pentaerythritol diphosphite, distearyl pentaerythritol diphosphite, or the like; alkylated monophenols or polyphenols; alkylation reaction products of polyphenols with dienes, such as tetrakis[methylene(3,5-di-tert-butyl-4-hydroxyhydrocinnamate)]methane, or the like; butylation reaction products of para-cresol or dicyclopentadiene; alkylated hydroquinones; hydroxylated thiodiphenyl ethers; alkylidene bisphenols; benzyl compounds; beta-(3,5-di-tert-butyl-4-hydroxyphenyl)-2,3-diphenyl ethers; butylated thiodiphenyl ethers; alkyl ... beta-(5-tert-butyl-4-hydroxy-3-methylphenyl)-propionic acid with mono- or polyhydric alcohols; esters of thioalkyl or thioaryl compounds such as distearyl thiopropionate, dilauryl thiopropionate, ditridecyl thiodipropionate, octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, pentaerythrityl-tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate or the like; amides of beta-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid or the like, or a combination comprising at least one of the foregoing antioxidants. Antioxidants may generally be used in amounts of 0.01 to 0.5 parts by weight, based on 100 parts by weight of the total composition, excluding any fillers.
[0086] In various embodiments, the thermoplastic composition may include a mold release agent. Exemplary mold release agents include, for example, metal stearates, stearyl stearates, pentaerythritol tetrastearate, beeswax, montan wax, paraffin wax, or the like, or a combination including at least one of the foregoing mold release agents. The mold release agents are generally used in an amount of about 0.1 to about 1.0 parts by weight based on 100 parts by weight of the total composition, excluding any fillers.
[0087] In one embodiment, the thermoplastic composition may include a heat stabilizer. By way of example, the heat stabilizer may include organic phosphites such as triphenyl phosphite, tris-(2,6-dimethylphenyl) phosphite, tris-(mixture of mono- and di-nonylphenyl) phosphite, or the like; phosphonates such as dimethylbenzene phosphonate, or the like; phosphates such as trimethyl phosphate, or the like, or a combination including at least one of the preceding heat stabilizers. The heat stabilizer may generally be used in an amount of 0.01 to 0.5 parts by weight based on 100 parts by weight of the total composition excluding any fillers.
[0088] In a further embodiment, light stabilizers can be present in the thermoplastic composition.Exemplary light stabilizers can include, for example, benzotriazoles such as 2-(2-hydroxy-5-methylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)-benzotriazole, and 2-hydroxy-4-n-octoxybenzophenone, or the like, or a combination that includes at least one of the above light stabilizers.The light stabilizer can generally be used in an amount of about 0.1 to about 1.0 parts by weight based on 100 parts by weight of the total composition, excluding any fillers.
[0089] The thermoplastic composition may also include a plasticizer. For example, the plasticizer may include phthalates such as dioctyl-4,5-epoxy-hexahydrophthalate, tris-(octoxycarbonylethyl)isocyanurate, tristearin, epoxidized soybean oil, or the like, or a combination comprising at least one of the foregoing plasticizers. Plasticizers are generally used in amounts of about 0.5 to about 3.0 parts by weight, based on 100 parts by weight of the total composition, excluding any fillers.
[0090] In a further aspect, the disclosed compositions can include antistatic agents, such as glycerol monostearate, sodium stearyl sulfonate, sodium dodecylbenzene sulfonate, or the like, or combinations of the above antistatic agents. In one aspect, carbon fibers, carbon nanofibers, carbon nanotubes, carbon black, or any combination of the above, can be used in polymeric resins containing chemical antistatic agents to make the compositions static dissipative.
[0091] Ultraviolet (UV) absorbers can also be present in the disclosed thermoplastic compositions. Exemplary UV absorbers include, for example; hydroxybenzophenones; hydroxybenzotriazoles; hydroxybenzotriazines; cyanoacrylates; oxanilides; benzoxazinones; 2-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)-phenol (CYASORB™ 5411); 2-hydroxy-4-n-octyloxybenzophenone (CYASORB™ 531); 2-[4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl]-5-(octyloxy)-phenol (CYASORB™ 1164); 2,2'-(1,4-phenylene)bis(4H-3,1-benzoxazin-4-one) (CYASORB™ 1164); UV-3638; 1,3-bis[(2-cyano-3,3-diphenylacryloyl)oxy]-2,2-bis[(2-cyano-3,3-diphenylacryloyl)oxy]methyl]propane (UVINUL™ 3030); 2,2′-(1,4-phenylene)bis(4H-3,1-benzoxazin-4-one); 1,3-bis[(2-cyano-3,3-diphenylacryloyl)oxy]-2,2-bis[[(2-cyano-3,3-diphenylacryloyl)oxy]methyl]propane; nano-sized inorganic materials such as titanium oxide, cerium oxide, zinc oxide, and the like, all having a particle size of less than 100 nanometers; or the like, or a combination comprising at least one of the foregoing UV absorbers. UV absorbers are generally used in amounts of 0.01 to 3.0 parts by weight, based on 100 parts by weight of the total composition, excluding any fillers.
[0092] The thermoplastic composition can further comprise a lubricant. For example, the lubricant can be fatty acid esters such as alkyl stearyl esters, for example methyl stearate, or the like; a mixture of methyl stearate with hydrophilic and hydrophobic surfactants, such as polyethylene glycol polymers, polypropylene glycol polymers, and copolymers thereof, for example methyl stearate with polyethylene-polypropylene glycol copolymers, in a suitable solvent; or a combination comprising at least one of the above lubricants. The lubricant can generally be used in an amount of about 0.1 to about 5 parts by weight, based on 100 parts by weight of the total composition, excluding any fillers.
[0093] Anti-drip agents can also be used in the composition, such as fibril-forming or non-fibril-forming fluoropolymers, such as polytetrafluoroethylene (PTFE). Anti-drip agents can be encapsulated by rigid copolymers, such as styrene-acrylonitrile copolymers (SAN). PTFE encapsulated in SAN is known as TSAN. In one example, TSAN can include 50 wt.% PTFE and 50 wt.% SAN, based on the total weight of the encapsulated fluoropolymer. SAN can include, for example, 75 wt.% styrene and 25 wt.% acrylonitrile, based on the total weight of the copolymer. Anti-drip agents, such as TSAN, can be used in amounts of 0.1 to 10 parts by weight, based on 100 parts by weight of the total composition, excluding any fillers.
[0094] As an example, the disclosed composition may include an impact modifier. The impact modifier may be a chemically reactive impact modifier. By definition, a chemically reactive impact modifier may have at least one reactive group such that the impact properties (expressed as Izod impact value) of a polymer composition improve when the impact modifier is added to the composition. In some examples, the chemically reactive impact modifier may be an ethylene copolymer having reactive functional groups selected from, but not limited to, anhydride, carboxyl, hydroxyl, and epoxy.
[0095] In a further aspect of the present disclosure, the composition may include a rubbery impact modifier. The rubbery impact modifier may be a polymeric material that is capable of substantially recovering its shape and size after removal of force at room temperature. However, it is typically desirable for the rubbery impact modifier to have a glass transition temperature of less than 0°C. In certain aspects, the glass transition temperature (Tg) may be less than -5°C, -10°C, -15°C, and preferably less than -30°C. g typically results in better performance. Exemplary rubbery impact modifiers can include, for example, functionalized polyolefin ethylene-acrylate terpolymers, such as ethylene-acrylic acid esters-maleic anhydride (MAH) or glycidyl methacrylate (GMA). The functionalized rubbery polymer can optionally contain repeat units in its backbone derived from anhydride group-containing monomers, such as maleic anhydride. In another scenario, the functionalized rubbery polymer can contain anhydride moieties that are grafted to the polymer in a post-polymerization step.
[0096] In one example, the composition may include a core-shell copolymer impact modifier having about 80 wt.% of a core including poly(butyl acrylate) and about 20 wt.% of a shell including poly(methyl methacrylate). In a further example, the impact modifier may include an acrylic impact modifier such as an ethylene-ethyl acrylate copolymer having an ethyl acrylate content of less than 20 wt.% (such as EXL 3330 supplied by Sabic). The composition may include about 5 wt.% of an ethylene-ethyl acrylate copolymer.
[0097] In many embodiments, the composition can be prepared according to a variety of methods. The compositions of the present disclosure can be blended, compounded, or otherwise combined with the preceding components by a variety of methods involving intimate mixing of the materials with any additional additives desired in the formulation. Melt-molding methods can be used since melt-mixing equipment is available in commercial polymer processing facilities. In various further embodiments, the equipment used in such melt-molding methods can include, but is not limited to, co-rotating and counter-rotating extruders, single screw extruders, co-kneaders, disc-pack processors, and various other types of extrusion equipment. In further embodiments, the extruder is a twin screw extruder. In various further embodiments, the composition can be processed in the extruder at a temperature of about 180°C to about 350°C, particularly 250°C to 300°C. Properties and Items
[0098] The disclosed combination of IDP, polycarbonate (PC) or its copolymers (ITR-BPAPC, SLX) with crystalline polymers also provides desirable ESD properties while maintaining a wide color space. The disclosed compositions also achieve balanced performance in electrical, aesthetics, impact resistance, and processing by combining the advantages of crystalline polymers and unique amorphous PC or PC copolymers.
[0099] In certain embodiments, the composition may exhibit static dissipative properties. For example, in some embodiments, the composition may exhibit a static dissipative property of 1×10 9 It may exhibit a surface resistivity of less than an ohm.
[0100] As provided herein, the compositions of the present disclosure are colorable. Colorable may describe the ease with which a polymeric composition can be colored. That is, the polymeric composition may be sufficiently "light" in color to accept dyes, pigments, or other color treatments / additives that impart a desired hue to the composition. Conventional dissipative materials often contain dark colored dissipative additives such as carbon fiber or carbon black. This may limit the color space for conventional ESD materials. The disclosed compositions have a colorlessness of 1×10 when tested according to ASTM D257. 9 These constraints may be alleviated by achieving sub-ohmic surface resistivity while at the same time being colorable. The values in this disclosure are given by the specific colorimetric coordinates L * , a * , b * It has a specific value for L * The "value" represents the lightness-darkness characteristic. * If the value is 0, the object is black. * If the value is 100, the object is white. * The value is always positive. L away from the extremes (0 and 100) * A composition having a higher L value will have a natural color, which may be a color selected for a particular application or may allow the composition to be more easily colored. * The further away from 0 and closer to 100 the value for L results in a composition having a wider "color space." A "color space" is a set of L that can be achieved using any colorant, pigment, and / or dye. * The range is L *may be measured using ASTM 2244 under 10 degree observer; Commission Internationale de Illumination (CIE) Standard Illuminant D65 illuminant; Specular Reflectance (SCI) reflectance; and large aperture. The polymeric composition has an L of at least about 50, or at least about 80, or at least about 90, as measured using a spectrophotometer under D65 illumination in reflectance mode and 10 degree observer. * It may indicate a color value.
[0101] Thus, these compositions are suitable candidates for consumer electronics / semiconductor / construction applications and can realize fundamentally important functions for ESD products with custom optimized colors.Furthermore, these compositions demonstrate the potential to replace filled ESD materials such as carbon fiber, conductive carbon black, graphite, graphene, carbon nanotubes, etc. in the market.
[0102] In various aspects, the present disclosure relates to an article comprising the composition herein.The composition can be molded into a useful molded article by various means, such as injection molding, extrusion, rotational molding, blow molding, and thermoforming, to form the article.The composition can be useful in the manufacture of articles that require materials with high modulus, good flowability, good impact strength, thermal conductivity, and reflectivity.
[0103] The advantageous properties of the compositions disclosed herein can be suitable for a range of applications.The formed articles can include, but are not limited to, personal computers, notebook computers, and portable computers, mobile phone antennas, and other such communication devices, medical applications, automatic identification technology RFID applications using near-field wireless communication, automotive applications, and the like.In various further embodiments, the articles can be suitable as the housings of computers and business equipment, such as high-end laptop personal computers, monitors, robotics housings, portable electronic device housings (such as housings or flash holders for smartphones, tablets, music devices), electrical connectors, light-emitting diode LED heat sinks, and lighting fixtures, wearable devices, decorations, parts of home appliances, and the like.
[0104] In further embodiments, non-limiting examples of fields in which the thermoplastic compositions may be employed include electrical technology, electromechanical technology, radio frequency (RF) technology, telecommunications, automotive, aviation, medical, sensors, military, and security, etc. In further embodiments, the thermoplastic compositions may also be found in overlapping fields, such as mechatronic systems that integrate mechanical and electrical properties that can be used in automotive or medical engineering.
[0105] In further embodiments, the suitable article can be an electronic device, an automotive device, a telecommunications device, a medical device, a security device, or a mechatronics device. In further embodiments, the article can be selected from a computing device, an electromagnetic interference device, a printed circuit, a Wi-Fi device, a Bluetooth device, a GPS device, a cellular antenna device, a smartphone device, an automotive device, a medical device, a sensor device, a security device, a shielding device, an RF antenna device, an LED device, and an RFID device. In further embodiments, the article can be selected from a computing device, a sensor device, a security device, an RF antenna device, an LED device, and an RFID device.
[0106] In a further embodiment, the molded article can be used to manufacture devices in the automotive field. In a further embodiment, non-limiting examples of devices in the automotive field for which the disclosed blended thermoplastic compositions can be used in the interior of a vehicle include cruise control and distance control devices, headlight sensors, windshield wiper sensors, and door / window switches. In a further embodiment, non-limiting examples of devices in the automotive field for which the disclosed blended thermoplastic compositions can be used in the exterior of a vehicle include pressure and flow sensors for engine control, air conditioning, collision detection, and exterior lighting fixtures.
[0107] In further aspects, the resulting disclosed compositions can be used to provide any desired shaped, formed, or molded article.For example, the disclosed compositions can be molded into useful shaped articles by various means, such as injection molding, extrusion, rotational molding, blow molding, and thermoforming.As mentioned above, the disclosed compositions are particularly suitable for use in the manufacture of electronic components and devices.Thus, according to some aspects, the disclosed compositions can be used to form articles such as printed circuit board carriers, burn-in test sockets, flex brackets for hard disk drives, and the like. Aspects
[0108] 1. A method for producing a polycarbonate copolymer, homopolymer, or blend thereof, comprising: about 0.1 wt.% to about 99 wt.% of a polycarbonate copolymer, homopolymer, or blend thereof; about 0.1 wt.% to about 70 wt.% of a crystalline polyester; about 0.1 wt.% to about 50 wt.% of an essentially dissipative polymer; and about 0.001 wt.% to about 10 wt.% of a transesterification inhibitor; and having a viscosity of 1×10 as measured according to ASTM D257. 9 1. A polymeric composition exhibiting a surface resistivity of less than ohms, wherein the combined weight percentage of all components does not exceed about 100 wt.%, all weight percentages being based on the total weight of the polymeric composition.
[0109] EMBODIMENT 1B. A composite material comprising: about 0.1 wt.% to about 99 wt.% of a polycarbonate copolymer, homopolymer, or blend thereof; about 0.1 wt.% to about 70 wt.% of a crystalline polyester; about 0.1 wt.% to about 50 wt.% of an essentially dissipative polymer; and about 0.001 wt.% to about 10 wt.% of a transesterification inhibitor; and having a viscosity of 1×10 as measured according to ASTM D257. 9 1. A polymeric composition exhibiting a surface resistivity of less than ohms, wherein the combined weight percentage of all components does not exceed about 100 wt.%, all weight percentages being based on the total weight of the polymeric composition.
[0110] EMBODIMENT 1C. A polymeric material consisting essentially of: about 0.1 wt.% to about 99 wt.% of a polycarbonate copolymer, homopolymer, or blend thereof; about 0.1 wt.% to about 70 wt.% of a crystalline polyester; about 0.1 wt.% to about 50 wt.% of an essentially dissipative polymer; and about 0.001 wt.% to about 10 wt.% of a transesterification inhibitor; and having a molecular weight of 1×10 as measured according to ASTM D257. 9 1. A polymeric composition exhibiting a surface resistivity of less than ohms, wherein the combined weight percentage of all components does not exceed about 100 wt.%, all weight percentages being based on the total weight of the polymeric composition.
[0111] Embodiment 2. The polymer composition of any one of embodiments 1A-1C, wherein the polycarbonate copolymer comprises ITR-BPAPC, BPAPC, or a combination thereof.
[0112] Embodiment 3. The polymer composition of any one of embodiments 1A-2, wherein the polyester comprises polybutylene terephthalate, polyethylene terephthalate, or 1,4-cyclohexanedimethyl-1,4-cyclohexanedicarboxylate), or a combination thereof.
[0113] Embodiment 4. The polymer composition of any one of embodiments 1A-3, wherein the inherently dissipative polymer comprises an ion-doped thermoplastic polyurethane (TPU) based multi-block copolymer.
[0114] Embodiment 5. The polymer composition of any one of Embodiments 1A-4, wherein the inherently dissipative polymer comprises an ion-doped nylon-based multi-block copolymer.
[0115] Aspect 6. An inherently dissipative polymer has a melting point of about 1×10 when tested in accordance with ASTM D257 on a 68 mm×68 mm×3 mm plaque specimen. 7 A polymer composition according to any one of embodiments 1A-5, having a surface resistivity in ohms.
[0116] Embodiment 7. The polymer composition of any one of Embodiments 1A-6, wherein the transesterification inhibitor comprises zinc monophosphate, a mixture of mono- and di-stearyl acid phosphate, or an alkyl acid phosphate.
[0117] Aspect 8. 1×10 when measured according to ASTM D257 6 Ohms and 1×10 9 The polymer composition of any one of embodiments 1A-8, exhibiting a surface resistivity of between ohms.
[0118] Aspect 9. An L of at least about 50 when measured using a spectrophotometer under D65 illumination in a reflective mode, 10 degree observer. * A polymer composition according to any one of embodiments 1A to 8, exhibiting a color value.
[0119] Aspect 10. An L of at least about 80 when measured using a spectrophotometer under D65 illumination in a reflective mode, 10 degree observer. * A polymer composition according to any one of embodiments 1A-9, exhibiting a color value.
[0120] Embodiment 11. The polymer composition of any one of Embodiments 1A-10, wherein the polymer composition is free or substantially free of carbon fibers, conductive carbon black, graphite, graphene, carbon nanotubes, or carbon nanostructures.
[0121] Embodiment 12. The polymer composition of any one of embodiments 1A-11, further comprising a polycarbonate-siloxane copolymer.
[0122] Embodiment 13. The polymer composition of any one of Embodiments 1A-11, further comprising an impact modifier.
[0123] Embodiment 14. The polymer composition of any one of embodiments 1A-13, wherein the polymer composition exhibits a deflection temperature under load of at least 90° C. when tested according to ASTM D648 at 0.45 MPa and 3.2 mm specimen thickness.
[0124] Embodiment 15. The polymeric composition of any one of Embodiments 1A-14, further comprising an optical brightener.
[0125] Embodiment 16. The polymer composition of embodiment 15, wherein the additive comprises a pigment, a dye, a filler, a plasticizer, a fiber, a flame retardant, an antioxidant, a lubricant, wood, glass, a metal, a UV agent, an antistatic agent, an antimicrobial agent, or a combination thereof. EXAMPLES
[0126] Although detailed embodiments of the present disclosure are disclosed herein, it should be understood that the disclosed embodiments are merely examples of the present disclosure that can be embodied in various forms. Therefore, the specific structural and functional details disclosed herein should not be interpreted as limitations, but merely as a basis for teaching those skilled in the art how to employ the present disclosure. The following specific examples will enable the present disclosure to be better understood. However, these are merely provided as guidelines and do not imply any limitations.
[0127] The following examples are provided to illustrate the compositions, processes, and properties of the present disclosure. The examples are merely illustrative and are not intended to limit the disclosure to the materials, conditions, or process parameters described therein. General Materials and Methods
[0128] The compositions described in the following examples were prepared from the ingredients shown in Table 1. Table 1. Components of the composition [Table 1]
[0129] The compositions described in the following examples were prepared from the ingredients shown in Table 1.
[0130] The formulations were prepared by extruding pre-blended components using a twin extruder. The polymeric resins (polycarbonate and polyester), IDP, inhibitors, and additives were premixed and fed through the main throat. The extrudate was cooled in a water bath before pelletizing. The components were compounded between 240°C and 250°C using a Toshiba™ TEM-37BS twin screw extruder. The compounding and molding conditions used are shown in Tables 2 and 3. The IDP has a high potential to react with the polycarbonate causing degradation and ultimately losing surface conductivity, so the processing temperature was maintained as much as possible. The specific combination of components overcame this technical hurdle and allowed low temperature processing as per this disclosure. Table 2. Compounding Conditions for Pigmentable ESD Polycarbonate Grades [Table 2] Table 3. Injection molding conditions for colorable ESD polycarbonate grades [Table 3]
[0131] The molded samples were tested according to the criteria set forth in Table 4. Table 4. Test criteria [Table 4]
[0132] The optical properties such as color and reflectance were measured using a ColorEye™ 7000A in reflection mode with a 10-degree observer under D65 illumination. The evaluation was performed using the colorimetric coordinates L of the International Commission on Illumination (CIE). * , a * , b * The coordinates correspond to different color attributes, and * are redness and greenness, b * is yellow and blue, L * represents the whiteness. * The value of L ranges between 0 and 100. * Values of L greater than 70 correspond to the darkness of the material. * A value of 0.01 appears nearly white to the naked eye.
[0133] Notched Izod impact ("NII") tests were performed according to ASTM D256 on 63.5 mm x 12.7 mm x 3.2 mm molded specimens (bars) at 25° C. Data units are J / m.
[0134] Unnotched Izod impact ("UNII") tests were performed according to ASTM D4812 on 63.5 mm x 12.7 mm x 3.2 mm molded specimens (bars) at 25° C. Data units are J / m.
[0135] The melt volume rate (MVR) was determined according to ISO 1133 at 220° C. and 2.16 kg.
[0136] Heat deflection temperatures were measured in a flat orientation at 0.45 megapascals (MPa) using 3.2 mm thick specimens (127 mm x 12.7 mm) according to ASTM D 648. Data are provided in °C.
[0137] Comparative samples C-1 and C-2 were prepared to evaluate the performance of formulations with and without a transesterification inhibitor. The comparative samples did not contain polycarbonate copolymer or polyester PBT 315. Table 5 (shown in Figure 1) summarizes the formulations and the observed properties (surface resistivity and L * )
[0138] The combination of nylon-based IDP and pure PC (C-1 and C-2 in Table 5) had a surface resistivity of 1×10 with or without additional transesterification inhibitors. 10 For EX-1, ITR-BPAPC copolymer SLX and PBT were used as building blocks to reduce the surface resistivity to 1×10 to meet ESD requirements. 9 The electrical conductivity of the SLX was reduced to ohms. The chemical resistance of SLX allows it to withstand the attack of nylon-based IDPs unscathed, and PBT, as a crystalline polymer, also resists nylon. In addition, PBT flows faster than amorphous PC and can carry the IDPs closer to the surface of the molded part, which is crucial for the formation of the conductive network.
[0139] The formulations in Table 5 were compounded with a small screw to prevent any thermal degradation. Additional samples were prepared using a conventional size screw for more general manufacturing purposes. The formulations and corresponding performance are presented in Table 6 (Figure 2).
[0140] EX-2 reproduced the results of EX-1, with a surface resistivity as low as E+9 ohms. HDT and notched Izod impact (NII) values were also still at high levels. Compared to the SLX / PBT of EX-1, EX-5 showed a 1x10 9 The surface resistivity did not remain in Ohms. For other crystalline polymers blended with SLX, PCCD in EX-4 achieved low surface resistivity, but not EX-3 with PET as polyester polymer system resin. EX-4 with IDP / SLX / PCCD also maintained high HDT and NII. For the blends of PC homopolymer with PET (EX-6) or PCCD (EX-7), the extruded strands could not be pelletized because they could not keep their shape. Without being bound to a particular theory, this may be attributed to the degradation of PC homopolymer, while SLX (ITR-BPAPC copolymer) showed good chemical resistance. Compared to the control sample C-3 (commercial grade name DD000), it can be seen that all our claimed formulations (EX-2 to EX-5) have significantly higher toughness as measured by notched Izod impact. In terms of freedom of processing, conventional conductive carbon black-filled PC (C-3) cannot be processed below 300°C, whereas EX-2 to EX-5 in Table 5.2 can all be injection molded at 220°C.
[0141] Additional IDPs were investigated. AvanDISS™ 378, manufactured by Avanzare, is not a nylon-based polymer and has not previously been considered to be as chemically aggressive towards PC as Pelectron™ AS. Table 7 (shown in Figure 3) presents three blends of AvanDISS™ 378 / SLX or PC homopolymer / PBT, which have a 1x10 9 It exhibited a low surface resistivity of 100 Ohms and also exhibited comparable thermal and mechanical properties.
[0142] The samples were also evaluated for optical properties by naked eye visual inspection and spectrophotometer. Another very important feature of the formulations was the nearly white appearance of all the listed blends. As shown in Figure 4A, the molded plate formed from the PC copolymer / PBT / IDP blend (EX-2) is white or light colored, thus allowing for further coloring. In Figure 4B, the conventional ESD material (C-3) appears completely black and has no potential for coloring. The L shown in Tables 5 and 6 * The values also quantitatively indicated the possibility of coloring. * The values are 90.6 and 82.5, respectively, suggesting a high possibility of further coloration. In the case of the control sample C-3 (conductive carbon black-filled PC), the observed L * The value was 26. This blackness or darkness inhibits any further color space.
[0143] The patentable scope of the present disclosure is defined by the claims, and may include other examples that occur to those skilled in the art. Such other examples are intended to be within the scope of the claims if they have structural elements that do not differ from the literal language of the claims, or if they include equivalent structural elements that have insubstantial differences from the literal language of the claims.
Claims
1. a) 45 wt. % to 85 wt. % of a polycarbonate component comprising a polycarbonate copolymer, a polycarbonate homopolymer, or a blend thereof; b) 1 wt. % to 30 wt. % of a crystalline polyester; c) 12 wt.% to 35 wt.% of an ion-doped polymer comprising an ion-doped thermoplastic polyurethane (TPU)-based multi-block copolymer or an ion-doped nylon-based multi-block copolymer; d) 0.001 wt.% to 10 wt.% of a transesterification inhibitor; A polymer composition comprising: less than 0.1 wt. % carbon fiber, conductive carbon black, graphite, graphene, carbon nanotubes, or carbon nanostructures; 1×10 when measured according to ASTM D257 9 exhibits a surface resistivity of less than ohms, An L of at least 50 when measured using a spectrophotometer under D65 illumination in reflectance mode, 10 degree observer * indicates the color value, A polymer composition, wherein the combined weight percentage of all components does not exceed 100 wt. %, and all weight percentages are based on the total weight of the polymer composition.
2. 2. The polymer composition of claim 1, wherein the a) polycarbonate component comprises a polycarbonate copolymer comprising ITR-BPAPC, BPAPC, or a combination thereof.
3. 3. The polymer composition of claim 1 or 2, wherein the b) crystalline polyester comprises polybutylene terephthalate, polyethylene terephthalate, or 1,4-cyclohexanedimethyl-1,4-cyclohexanedicarboxylate, or a combination thereof.
4. The ion-doped polymer exhibited a 1×10 solubility when tested according to ASTM D257 on a 68 mm×68 mm×3 mm plaque specimen. 7 3. The polymer composition of claim 1, having a surface resistivity in ohms.
5. The polymer composition of claim 1 or 2, wherein the transesterification inhibitor comprises zinc monophosphate, a mixture of mono- and di-stearyl acid phosphate, or an alkyl acid phosphate.
6. 1×10 when measured according to ASTM D257 6 Ohms and 1x10 9 3. The polymer composition of claim 1, exhibiting a surface resistivity of between ohms.
7. An L of at least 80 when measured using a spectrophotometer under D65 illumination in reflectance mode with a 10 degree observer * 3. The polymer composition of claim 1 or 2, exhibiting a color value.
8. 3. The polymer composition of claim 1 or 2, further comprising a polycarbonate-siloxane copolymer different from said a) polycarbonate component.
9. 3. The polymer composition of claim 1 or 2, further comprising an impact modifier.
10. 3. The polymer composition of claim 1 or 2, exhibiting a deflection temperature under load of at least 90° C. when tested according to ASTM D648 at 0.45 MPa and 3.2 mm specimen thickness.
11. 3. The polymer composition of claim 1 or 2, further comprising an optical brightener.
12. 3. The polymer composition of claim 1 or 2, further comprising additional additives comprising pigments, dyes, fillers, plasticizers, fibers, flame retardants, antioxidants, lubricants, wood, glass, metals, UV agents, antistatic agents, antimicrobial agents, or combinations thereof.
Citation Information
Patent Citations
Permanent antistatic polycarbonate film or sheet and production thereof
JP1998219095A
Conductive Polyester / Polycarbonate Blends, Methods of Making Them and Resulting Products
JP2004514782A
Electrostatic dissipative resin composition and method for producing the same
JP2006511668A
Broadening of Percolation Slope in Conductive Carbon Black Compositions with at least One Non-Conductive Polymer
US20140197367A1
Multifunctional flame retardant thermoplastic compositions for connected personal protective equipment
US20190169429A1